Answer:
m = -2 and n = 10
Explanation:
If the polynomial mx^3 - 3x^2 + nx + 2 is divided by x + 3, the remainder is -1. Then;
x+ 3 = 0
x = -3
Substitute x =-3 into the polynomial and equate to -1
-1 = m(-3)³-3(-3)²+n(-3) + 2
-1 = -27m - 27 - 3n + 2
27m + 3n = -25 + 1
27m + 3n = -24 ... 1
Similarly, if it is divided by x - 2, the remainder is -4, then;
-4 = m(2)³-3(2)²+n(2) + 2
-4 = 8m - 12- 2n + 2
8m -2n = -4 + 10
8m + 2n = 6 ... 2
Solve 1 and 2 simultaneously
27m + 3n = -24 ... 1 * 2
8m + 2n = 6 ... 2 * 3
______________________
54m + 6n = -48
24m + 6n = 12
54m - 24m = -48 - 12
30m = -60
m = -60/30
m = -2
Get n by substituting m = -2 into 1
From 1: 27m + 3n = -24
27(-2) + 3n = -24
-54 + 3n = -24
3n = -24 +54
3n = 30
n = 30/3
n = 10
Hence m = -2 and n = 10